THE ANALYSIS OF THE EFFECT OF SERVICE QUALITY, PRICE AND WORD-OF-MOUTH ON CUSTOMER SATISFACTION AT GRAND KUPI BLANG PULO - Radja Alvarezi; Halida Bahri (CV. Radja Publika, 2026)
This study aims to analyze the influence of service quality, price, and word-of-mouth on customer satisfaction at Grand Kupi Blang Pulo, a local coffee shop in Lhokseumawe City. The background of this research is the decline in Grand Kupi's revenue over the past three years, indicating potential issues in customer satisfaction. A quantitative approach was used with a survey method involving 100 respondents who were customers of Grand Kupi. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that service quality, price, and word-of-mouth simultaneously have a significant effect on customer satisfaction. Partially, service quality and word-of-mouth have a positive and significant influence, while price also has a significant impact, albeit with a lower contribution. These findings highlight the importance of improving service quality and optimizing word-of-mouth strategies to maintain and enhance customer satisfaction .